Web application development: BITM 2113 - Devaraju, Anusuriya (Penerbit Kolej Universiti Teknikal Malaysia Melaka, 2006)
This laboratory module aimed primarily for students who will be taking subject BITM 2113 from FTMK, KUTKM. It provides the students with practical knowledge on web programming, including: Mark-up Languages: HTML, XHTML, XML; Client-side Scripting: JavaScript; Server Site Scripting: PHP; Database Server. MySQL and Web Server: IIS and Apache. The hands-on practice is to equip the students with a basic range of skills required for designing web-based applications. The emphasis is on familarizing readers with the range of website development languages, rather than too much emphasis on aethetic issues, such as graphic design.